Design of oscillating-water-column wave energy converters with an application to self-powered sensor buoys. (1st October 2016) - Henriques, J.C.C.; Portillo, J.C.C.; Gato, L.M.C.; Gomes, R.P.F.; Ferreira, D.N.; Falcão, A.F.O.
Abstract: The quest for conquering the ocean and understanding its behaviour has been a challenge with increasing needs for innovation and technology investments in many areas of strategic value for the promotion, growth and competitiveness of the marine economy worldwide. Current oceanographic buoy systems are limited to low power levels and intermittency of data acquisition and transmission, among other aspects that need to be overcome to comply with new and more demanding applications. The development of marine activities requires more powerful and reliable data-acquisition systems to guarantee their future sustainability. This work presents a new systematic methodology for optimum design of wave energy converters. The methodology was applied to design two self-powered sensor buoys for long term monitoring based on the oscillating-water-column principle. The optimisation focussed on buoy hydrodynamic shape, sizing and selection of the turbine and the generator, as well as the control law of the generator electromagnetic torque. The performance was assessed through the use of the power matrix and a set of performance indicators. These performance indicators were defined to allow a simple comparison between different wave energy concepts. The results confirm the applicability of the designed buoys for a next generation of oceanographic monitoring systems. Highlights: A new methodology was proposed for optimum design of oscillating water column devices. The optimisation focussed on buoy hydrodynamics and power take-off design. The performance was assessed through the power matrix and a set of indicators. The new design methodology was applied to two self-powered sensor buoys. Floating OWC buoys are promising alternatives to conventional sensor buoys.